Bold ambition, blunted agency? Examining top management perspectives on a circular economy transition in Finland - Koistinen Katariina; Onkila Tiina; Teerikangas Satu; Mäkelä Marileena; Sarja Milla; Valkjärvi Mira (Elsevier, 2022)
The circular economy is proposed as a company-driven means to further sustainability transitions. Top managers have a critical role in fostering the circular economy as they are responsible for shaping and implementing a company's sustainability strategy and performance. In this paper, we adopt a microfoundations perspective to enhance our understanding of the influence of top managers as agents of the sustainability transition to the circular economy. In a qualitative research study, we interviewed 34 top managers of Finnish companies that are actively pursuing the circular economy. The main implication of our study is in exploring the role of top managers, as they engage in actively structuring a new, circular regime. To this end, our paper provides salient insights into the prevailing debate on the structure-agency question in the sustainability transitions literature. We find that power is a key characteristic of how top managers exercise their agency. Our findings imply that while top managers are perceived as the most powerful members of a company, their agency is often limited by structural constraints on multiple levels within their companies, in the industry, and in the broader regime. Furthermore, we find that top managers' power and agency towards the transition is heavily dependent on their abilities to secure business profitability.